Assessing the responsiveness of supply chain - structural equation modelling based approach. Issue 4 (2016) - Raghuram, P.; Saleeshya, P.G.
Companies worldwide have now realised that 'customer focus' is what wins the game. As demands of the customer become more and more volatile and unpredictable, they have to stay ahead of their competitors in fulfilling the needs of the customer. The supply chain as a 'unit' has to compete against other supply chains for reaching out and delighting the customer. Responding fast to the changing customer needs has been an intangible factor underlying a successful business. Thus, responsiveness of the supply chain has become the differentiator between the competing supply chains. In this paper, the end-to-end supply chain factors influencing responsiveness are identified from extant literature and a model of responsiveness of the supply chain has been developed by conducting a survey of 204 pump manufacturers. The developed model has been validated through confirmatory factor analysis using structural equation modelling. These findings can help to identify the areas of improvement for the supply chain and may lead to a focused improvement in these areas thus improving responsiveness and profitability.